Densidade mamográfica e polimorfismos do gene do receptor de estrogênio MspI e do receptor de progesterona PROGINS em índias do estado do Amapá - Secco, Jose Mauro [UNIFESP] (2013)
Background: Mammographic density is known to be one of the main risk factors for breast cancer and presents individual variations due to various factors. It is also of scientific knowledge that the indigenous groups present less dense breasts compared with non-indigenous populations, and that breast cancer is rare in this ethnic group. This study aims to evaluate the clinical characteristics of indigenous population of the state of Amapá and also the MspI and PROGINS polymorphisms of the estrogen and progesterone receptor genes, associating them with the mammographic density in indians who had never undergone mammography. Knowing that the clinical characteristics and sex steroids affect mammographic density, we sought the finding of low mammographic density in this population and some explanation for the difference in mammographic density and in breast cancer incidence. Methods: We studied 135 women of indian ethnicity without clinical or mammographic alterations and who had never used hormone therapy. All of them were transported to the state capital Macapá to undergo interview, bilateral mammography and collection of biological material. The interview was held at the Indian House through local interpreter; mammographic density was determined by three independent observers, two subjective evaluations were based on the classification of the ACR-BI-RADS® 2003 and another was computerized (software Adobe PhotoshopÒ, v. 10.0). Blood samples were taken for DNA extraction according to the illustra Kit protocol (GE Healthcare) and then PCRRFLP (polymerase chain reaction - restriction fragment polymorphism length) was held for analysis of MspI and PROGINS polymorphisms in the estrogen and the progesterone receptor genes. Result: High agreement was found in mammographic density between observers through Pearson's correlation coefficients R, Spearman Correlation and Kappa, with p = 0.001. We found 82% of Indian women with not dense breasts and 18% with dense breasts, with a mean age of 50.4 years. The clinical characteristics associated with mammographic density were age (p = 0.0001), FSH levels (p < 0.001) and estrogen levels (p < 0.01). There was no statistical difference between the groups of dense and not dense breasts for PROGINS and ER-MspI polymorphisms genotypes. Conclusion: Mammographic density in indian women is predominantly low, regardless of menopausal status. Mammographic density is significantly associated with age menopausal status, FSH and E2 levels in this population. The PROGINS polymorphism was found in 3.7% of the women and Mspl in 84.4%. No correlation was found of polymorphism with mammographic density.